Trends in the Incidence of Bacteremia with Carbapenem Non-susceptible Acinetobacter spp. in Patients from the US Veterans Health Administration, 2000–2015. (4th October 2017) - Patel, Sachin; Wilson, Brigid; Chakhtoura, Nadim G. El; Saade, Elie; Donskey, Curtis; Bonomo, Robert A; Perez, Federico
Abstract: Background: Carbapenem-resistant Acinetobacter is considered a critical priority pathogen by the WHO and CDC. Formerly, this organism was a major pathogen in health care facilities caring for US soldiers wounded in Iraq and Afghanistan. We use the unique vantage point of the US Veterans Health Administration (VHA) to monitor nationwide trends in the epidemiology of Acinetobacter . Methods: Using VHA databases, we identified Acinetobacter species isolated from blood cultures in patients hospitalized from 2000 to 2015 at VHA facilities. Repeat cultures within 90 days were only counted once. Facilities were classified according to regions designated by the US Department of Health and Human Services (HHS). We examined the proportion of isolates with carbapenem non-susceptibility (NS), calculated incidence of bacteremia per 10, 000 admissions in each region yearly, and determined mortality at 30 days. Results: We analyzed 3, 306 patients with Acinetobacter bacteremia admitted to VHA facilities between 2000 and 2015. Rate of carbapenem NS increased from 4% in 2000 to 37% in 2009. In contrast, it decreased to 18% in 2015. Mortality at 30 days was significantly higher in patients with carbapenem NS Acinetobacter bacteremia (37% vs. 21%). The incidence of carbapenem NS Acinetobacter bacteremia was highest in region 2 (includes New York, New Jersey and Puerto Rico) where it peaked at 5.65 and 5.1 cases per 10, 000 admissions in 2003 and 2006. Other significant peaks between 2006 and 2009 occurred in region 3 (includes Maryland) with 2.12 cases per 10, 000 admissions, region 6 (includes Texas) with 2.27 cases per 10, 000 admissions, and region 9 (includes California) with 3.57 cases per 10, 000 admissions. After 2013, the incidence of carbapenem NS Acinetobacter bacteremia declined in all HHS regions, ranging between 0 and 1 cases per 10, 000 admissions (see figure). Conclusion: This analysis of VHA data reveals differing regional trends and a recent decrease in the overall incidence of carbapenem-NS Acinetobacter bacteremia, a condition associated with high mortality. A robust surveillance system integrating genetic characterization, infection control practices and antibiotic use data is needed to understand the changing epidemiology of Acinetobacter . Disclosures: E. Saade, Steris: Grant Investigator, Grant recipient. Janssen: Grant Investigator, Research grant. Sequiris: Grant Investigator, Research grant. Pfizer: Grant Investigator, Research grant. R. A. Bonomo, Entasis: Grant Investigator, Research grant. Allecra: Grant Investigator, Research grant. Wockhardt: Grant Investigator, Research grant. Merck: Grant Investigator, Research grant. Roche: Grant Investigator, Research grant. GSK: Grant Investigator, Research grant. Allergan: Grant Investigator, Research grant. Shionogi: Grant Investigator, Research grant. F. Perez, Merck: Grant Investigator, Grant recipient. Achaogen: Scientific Advisor, Consulting fee. Allergan: Scientific Advisor, Consulting fee. Pfizer: Grant Investigator, Educational grant